Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning pada Kelas V Sekolah Dasar - Oktalativa, Wahyuni; Taufina, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to describe the improvement of integrated thematic learning processes using the Problem Based Learning model for class V SD Negeri 09 Bandar Buat kota Padang. This type of research is classroomaction research with quantitative and quantitative approach. The research data was obtained from the RPP observation sheet, teacher aspects, student aspects and test sheets. The study was conducted in two cycles. Cycle I had II meetings and Cycle II had one meeting. One cycle consists of planning, implementing, observing, and reflecting. The research subjects were teachers and 30 fifth grade students V SD Negeri 09 Bandar Buat Kota Padang.The results the first cycle study RPP 75% (C), increasing to 93.75% (SB). in cycle 2. (2) the aspect assessment of cycle 1 teachers gained an average grade of 75% (C) increasing to 87.5% (B) in cycle 2. The assessment of aspects of cycle 1 students gained an average grade of 75% (C), increased to 87.5% (B) in cycle 2. Student learning outcomes cycle 1 obtained an average value of 65.21% (C) and increased cycle 2 to 93.6 % (SB). Thus, the Problem Based Learning model can improve the integrated thematic learning process.